Pertanggungjawaban Perdata Bank NTB Syariah Terkait Hilangnya Dokumen Jaminan Kredit Nasabah : (Analisis Putusan Nomor 245/Pdt.G/2018/PN.Mtr) - Assyifa Gema Ayu Mandalika; Rahmawati Kusuma (Private Law, 2022)
This study aims to determine the basis for the judge's considerations in Decision Number 245/PDT.G/2018/PN.Mtr and the legal consequences arising from the loss of customer credit guarantee documents at Bank NTB. The method used by the author in this study is a normative research method. The result of the research is that the Panel of Judges stated that the Defendant's actions were against the law so that the Defendant had to pay compensation to the Plaintiff and pay the court costs incurred in this trial as a result of the unlawful acts committed.